Evolutionary game of cooperative decision-making in reverse supply chain based on cooperative effort. Issue 1 (March 2021) - Lin, Ni; Yuli, Xiong
Abstract: Aiming at a large number of end-of-life (EOF) electrical products flowing into individual recycling outlets, it will squeeze the living space of formal dismantling companies and cause secondary pollution problems. The purpose of this paper is to establish a stable cooperative relationship between them to guide EOF products flowing from individual recycling outlets into the formal dismantling process. A game model involving the participation of formal dismantling enterprises and individual recycling outlets is constructed, and the role of government punishment mechanism intervention in the formation of active cooperative relations between participants in different parameter ranges is discussed. Then, the stability of the evolutionary equilibrium point is analysed. Finally, the Matlab software is used to simulate the influence of parameter on the formation of a stable cooperative relationship, and suggestions for promoting cooperation are provided.